Exploration of Molecular Structure, DFT Calculations, and Antioxidant Activity of a Hydrazone Derivative - Kundan Tayade; Gyu-Seong Yeom; Suban K. Sahoo; Horst Puschmann; Satish Balasaheb Nimse; Anil Kuwar (MDPI AG, 2022)
The hydrazine derivatives are known to possess several biological activities including anticancer, antibacterial and anti-fungal, anticonvulsant, and antioxidant. This communication presents the synthesis, X-ray crystal structure analysis, DFT calculations, cell cytotoxicity, and antioxidant activity of the Schiff base 4,4'-((1E,1'E)-hydrazine-1,2-diylidenebis(ethan-1-yl-1-ylidene))bis(benzene-1,3-diol) (compound 2). We have also isolated the side product compound 1 and characterized it using single X-ray crystallography. The crystal structure of compound 1 depicts that the ensuing C-H···N hydrogen bonding interaction is presented and discussed herein. In addition, the calculations using density functional theory (DFT) approximation supported by experimental 1H and 13C NMR studies on the key compound 2 are reported. The results of theoretical and experimental 1H and 13C NMR were concordant. The antioxidant activity of compound 2 was determined by using 2,2'-azinobis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS•+) radical cation assays and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical assay. Compound 2 demonstrated excellent antioxidant activity in ABTS assay (IC50 = 4.30 ± 0.21 µM) and DPPH assay (IC50 = 81.06 ± 0.72 µM) with almost no cytotoxicity below 25 µM.